Policy to Accelerate Handling and Prevention of Stunting in Pakpak Bharat Regency - Ti Aisyah; Lidia Burunea; Syamsuddin Syamsuddin; Aiyub Aiyub; Ahmad Yani; Muhammad Hasyem (Universitas Pahlawan Tuanku Tambusai, 2026)
The policy for accelerating and handling stunting in West Pakpak Regency is a priority policy that must be implemented optimally considering the still high number of stunting in the Regency , even though the government has established policies and programs to accelerate the prevention and handling of stunting with the aim of reducing the number. s tuning . Stunting remains a serious problem with long-term impacts on the quality of human resources, making its handling a priority in public health development. The purpose of this study is to analyze how the policy for accelerating the prevention and handling of stunting is implemented in Pakpak Bharat Regency and the factors that hinder its success. This study uses a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. Data analysis techniques use an interactive model through the stages of data collection, data reduction, data presentation , and drawing conclusions. The results show that the policy for accelerating the prevention and handling of stunting in the Pakpak Bharat region has established several prevention and handling program activities, including the provision of supplementary feeding (PMT), vitamin A provision, and counseling. However, their implementation has not been optimal. Both counseling activities, vitamin A provision, and PMT distribution have not been implemented properly to the target community. Several factors that hinder the implementation of the program policy include low parental knowledge, weak networks, and limited access to health services. communication facilities, less supportive socio-economic and political conditions. In addition, the distribution of supplementary food for stunted children is not yet effective, so the nutritional value is low. Children are not receiving optimal support. Difficult road access to remote villages is also a major obstacle in distributing aid and implementing programs. Therefore, evaluation and improvement are needed. implementation of policies to accelerate prevention and handling of stunting.